Thyroid Gland Development and Function 2007
DOI: 10.1159/000106821
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of Thyroid Function and Interactions with Maternal Function

Abstract: Fetal and neonatal development of thyroid function involves the embryogenesis, differentiation and maturation of the thyroid gland, of the hypothalamic-pituitary-thyroid axis and of the systems controlling thyroid hormone metabolism. We focus here on aspects related to neurodevelopment. Throughout gestation, thyroxine (T4) transferred from the mother, present in embryonic fluids by 4 weeks, protects the fetal brain. Free T4 (FT4) in fetal fluids increases rapidly, approaching adult levels by midgestation, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 34 publications
3
65
0
1
Order By: Relevance
“…Our observations indicate T 3 degradation but not production in the fetal hypothalamus at this moment in development. This supports the notion that during early development, the brain is protected against high T 3 concentrations to prevent untimely maturation of brain cells (16). Earlier studies have suggested that at 18 weeks of gestation, all T 3 in the brain is produced via local deiodination (26).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our observations indicate T 3 degradation but not production in the fetal hypothalamus at this moment in development. This supports the notion that during early development, the brain is protected against high T 3 concentrations to prevent untimely maturation of brain cells (16). Earlier studies have suggested that at 18 weeks of gestation, all T 3 in the brain is produced via local deiodination (26).…”
Section: Discussionsupporting
confidence: 81%
“…Rodent studies have shown that during development, D2 expression is low, while D3 expression is high. This mechanism of low triiodothyronine (T 3 ) during gestation has been proposed to prevent untimely maturation of brain cells (16). A similar mechanism of coordinated expression of D2 and D3 has been shown in cochlear development and during brown adipogenesis, where absence of either deiodinase leads to inappropriate levels of T 3 and results in deafness or impaired adaptive thermogenesis of brown adipose tissue respectively (17,18,19).…”
Section: Introductionmentioning
confidence: 90%
“…The various TRa (THRA) and TRb (THRB) isoforms are expressed in the fetus in a tissuespecific manner by mid-gestation and often at gestational ages earlier than the appearance of thyroid hormones in the fetal circulation (Table 1; Bernal & Pekonen 1984, Nagasawa et al 1997, White et al 2001, Chan et al 2002. These findings indicate that, for some species, maternal thyroid hormones may contribute to the control of early embryonic growth and development, before the onset of fetal thyroid hormone activity (Obregon et al 2007). In addition, there are developmental changes in TR binding in the fetal brain, lung, skeletal muscle, liver, and heart as term approaches, which are also species specific (Bernal & Pekonen 1984, Perez-Castillo et al 1985, Ferreiro et al 1987, Polk et al 1989, Falcone et al 1994, White et al 2001.…”
Section: Thyroid Hormone Transporters and Receptors In Fetal Tissuesmentioning
confidence: 99%
“…This is crucial because the brain is dependent on T3 for optimal development. The fetal contribution to fT4 and T4 increases until birth (23). However, maternal transfer of T4 to the fetus continues until the umbilical cord is severed (24).…”
Section: Endocrinological Parameters and Neuromotor Outcomementioning
confidence: 99%